Platinum(II) as Bifunctional Linker in Antibody–Drug Conjugate Formation: Coupling of a 4‐Nitrobenzo‐2‐oxa‐1, 3‐diazole Fluorophore to Trastuzumab as a Model. Issue 5 (25th March 2015) - Waalboer, Dennis C. J.; Muns, Joey A.; Sijbrandi, Niels J.; Schasfoort, Richard B. M.; Haselberg, Rob; Somsen, Govert W.; Houthoff, Hendrik‐Jan; van Dongen, Guus A. M. S.
Abstract The potential of platinum(II) as a bifunctional linker in the coordination of small molecules, such as imaging agents or (cytotoxic) drugs, to monoclonal antibodies (mAbs) was investigated with a 4‐nitrobenzo‐2‐oxa‐1, 3‐diazole (NBD) fluorophore and trastuzumab (Herceptin™) as a model antibody. The effect of ligand and reaction conditions on conjugation efficiency was explored for [Pt(en)(L‐NBD)Cl](NO3) (en=ethylenediamine), with L=N‐heteroaromatic, N‐alkyl amine, or thioether. Conjugation proceeded most efficiently at pH 8.0 in the presence of NaClO4 or Na2SO4 in tricine or HEPES buffer. Reaction of N‐coordinated complexes (20 equiv) with trastuzumab at 37 °C for 2 h, followed by removal of weakly bound complexes with excess thiourea, afforded conjugates with an NBD/mAb ratio of 1.5–2.9 that were stable in phosphate‐buffered saline at room temperature for at least 48 h. In contrast, thioether‐coordinated complexes afforded unstable conjugates. Finally, surface plasmon resonance analysis showed no loss in binding affinity of trastuzumab after conjugation.